Evidence for production of single top quarks and first direct measurement of |Vtb| - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
The D0 Collaboration presents first evidence for the production of single top quarks at the Fermilab Tevatron pp̄ collider. Using a 0.9fb-1 dataset, we apply a multivariate analysis to separate signal from background and measure σ(pp̄→tb+X,tqb+X)=4.9±1.4pb. The probability to measure a cross section at this value or higher in the absence of a signal is 0.035%, corresponding to a 3.4 standard deviation significance. We use the cross section measurement to directly determine the Cabibbo-Kobayashi-Maskawa matrix element that describes the Wtb coupling and find 0.68<|Vtb|≤1 at 95% C.L. within the standard model. © 2007 The American Physical Society.